Stock Price Analysis of Automotive Company Listed on IDX 2018-2022 - Mayasari, Asri; Setiawati, Ira; Darmaputra, Mochamad Fadjar (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
This study aims to determine the effect of the Return On Equity(ROE), Current Ratio (CR), Debt To debt-to-equity ratio (DER), and earnings per Share(EPS). The population of this research is 40 automotive companies listed on the Indonesian Stock Exchange (IDX) from 2018-2022. This research used purposive sampling and obtained a sample of 8 companies using the method of documentation, the users of data derived from documents that already exist and are published on the Indonesian Stock Exchange’s website. Data analysis using multiple regression. The result of the analysis indicates that Return On Equity has a significant positive effect on stock price, Debt To Equity Ratio has no positive significant effect on stock price, and Earnings per share have a significant effect on automotive stock prices and components in the research sample. This can be seen from the significant value which is smaller than 0.05.